(untitled) (Veterinary Science, 2024)
Community Practices (CPs) are teaching and learning spaces, where scientific and community knowledge are compromised to address real problems. At FCV UNLPam the CPs began to be implemented in 2018 and are mandatory to obtain the degree. The objective was to analyze the conception of CPs and its connection with teaching, extension and research at the Faculty of Veterinary Sciences of the National University of La Pampa (FCV-UNLPam) during the years 2018 – 2023. A qualitative quantitative research was carried out. The regulatory framework and CPs proposals were reviewed. Surveys were carried out on students and interviews with teachers/tutors who participated in the CPs. The participating subjects, the activities carried out and the link with the study plan were analyzed. The ideas, feelings, objectives, learning achieved, positive aspects, difficulties and challenges were investigated. The proposals presented were linked to the professional profile. CPs related to the prevention of zoonoses, vaccination campaigns, and work with small goat and pig producers were carried out. The CPs were valued as training spaces, which allowed us to learn about other realities, link theory with practice and discover other professional fields. It is necessary to re-signify them from the social function of the university and from a critical perspective. The CPs are opportunities to integrate work in the territory into the curriculum. In addition, intersectoral, interdisciplinary approaches and comprehensive practices are promoted.